India and China the way forward - Rajan, D.S (Chennai Centre for China Studies KW Publishers Pvt Ltd, 2013)
The book marks the publication of papers presented at a National Seminar on 'India and China: The way Forward', organised, by the Chennai Centre for China Studies (C3S),at Chennai on March16, 2012. The participants included eminent Sinologists in the country representing the academic community, former bureaucrats who covered China as part of their duties, and experts with security and military background. The book is being brought out with the objective of ensuring wider dissemination of their views.